ANALISIS PENERAPAN JUAL BELI BAI SALAM DALAM MENINGKATKAN KESEJAHTERAAN PETANI - Tiara Pitri; Eja Armaz Hardi; Fauzan Ramli (CV. Aksara Global Akademia, 2023)
Salam buying and selling transactions are a form of buying and selling transactions with payment in advance and delivery of goods at a later date in accordance with the price, specifications, quantity, quality, residence and place of delivery, as well as previously agreed in the contract. Salam buying and selling transactions are transactions that are usually carried out by the people of Rantau Alai Village when the sale and purchase of palm oil is agreed. This research is entitled